Cell type–specific purifying selection of synonymous mitochondrial DNA variation - Caleb A. Lareau; Patrick Maschmeyer; Yajie Yin; Jacob C. Gutierrez; Ryan S. Dhindsa; Anne-Sophie Gribling-Burrer; Sebastian Zielinski; Yu-Hsin Hsieh; Lena Nitsch; Veronika Dimitrova; Benan Nalbant; Frank A. Buquicchio; et al. (Proceedings of the National Academy of Sciences, 2025)
While somatic variants are well-characterized drivers of tumor evolution, their influence on cellular fitness in nonmalignant contexts remains understudied. We identified a mosaic synonymous variant (m.7076A > G) in the mitochondrial DNA (mtDNA)-encoded cytochrome c-oxidase subunit 1 (MT-CO1, p.Gly391=), present at homoplasmy in 47% of immune cells from a healthy donor. Single-cell multiomics revealed strong, lineage-specific selection against the m.7076G allele in CD8 + effector memory T cells, but not other T cell subsets, mirroring patterns of purifying selection of pathogenic mtDNA alleles. The limited anticodon diversity of mitochondrial tRNAs forces m.7076G translation to rely on wobble pairing, unlike the Watson–Crick–Franklin pairing used for m.7076A. Mitochondrial ribosome profiling confirmed stalled translation of the m.7076G allele. Functional analyses demonstrated that the elevated translational and metabolic demands of short-lived effector T cells (SLECs) amplify dependence on MT-CO1, driving this selective pressure. These findings suggest that synonymous variants can alter codon syntax, impacting mitochondrial physiology in a cell type–specific manner.